Nutritional Composition and Volatile Compounds of Black Cumin (Nigella sativa L.) Seed, Fatty Acid Composition and Tocopherols, Polyphenols, and Antioxidant Activity of Its Essential Oil - Zainab Albakry; Emad Karrar; Isam A. Mohamed Ahmed; Emel Oz; Charalampos Proestos; Aly Farag El Sheikha; Fatih Oz; Gangcheng Wu; Xingguo Wang (Horticulturae, 2022)
This study was to assess the nutritional quality and bioactive properties of black cumin (Nigella sativa L.) seeds and oil commonly found in the Chinese market. The results showed that black cumin seeds contain 5.02, 21.07, 39.02, 3.02, 6.01, and 25.86% moisture, crude proteins, crude fat, ash, fiber, and carbohydrates, respectively. It also contains substantial amounts of minerals, namely calcium, potassium, phosphorus, magnesium, sodium, iron, zinc, and copper. Glutamic acid (4.10 g/100 g protein) is the major amino acid of black cumin seeds. The major volatile components in black cumin seeds were thymoquinone (21.01%), o-cymene (18.23%), and β-thujene (17.22%). Cumin seed oil extracted by the soxhlet method contains high quantities of unsaturated fatty acids (UFA; 85.16%) and low amounts of saturated fatty acids (SFA; 15.02%). The major fatty acid of black cumin seed oil was linoleic acid (57.71%), followed by oleic acid (24.46%). The most prominent TAG of black cumin seed oils was oleoyl-dilinoleoyl-glycerol (OLL; 38.87%). In addition, the levels of α-tocopherol, β-tocopherol, γ-tocopherol, and total polyphenols in the black cumin seed oil were 25.59, 14.21, and 242.83 mg/100 g, and 315.68 mg GAE/kg, respectively, and possessed high antioxidant activity (DPPH IC50%, of 4.02 mg/mL). These findings demonstrate that black cumin seeds are nutritionally rich with high potential applications in the food, pharmaceutical, and cosmetic industries.